AUTHOR’S PRAYER IN THE WORK OF WІRA WOWK - Григорчук , Юлія (Кафедра полоністики Навчально-наукового інституту філології Київського національного університету імені Тараса Шевченка, 2022)
The article is devoted to the analysis of the genre of the author’s prayer in the literary works of Wіra Wowk. The object of study for the first time was not only poetic, but also the writer’s prose and dramatic texts. The analysis of biographical and literary works testified that the genre of prayer is an integral part of the Wіra Wowk’s work. This genre is multivariate embodied in the writer’s prose, poetry and drama. On the basis of the analysis of biographical and literary criticism, the organicity of the genre of prayer in the work of Vira Vovk and the specifics of his embodiment in prose, poetry and drama is emphasized. It is noted that short aphoristic verses and prayers are characteristic of poetry, and long prayers and meditations are characteristic of prose and drama. The writer puts prayers in the context of the work (characters’ prayers) or introduces them into the plot as inserted elements (author’s prayers). These are prayer-requests, thank-you prayers and prayers-glorification, and also prayers-confessions and prayer-reflexions. Their recipients are the Lord God, the Virgin Mary and the saints (Teresa of Lisieux, Francis of Assisi, Nicholas of Myra). The topics of these prayer texts cover the themes of creativity, spiritual quest, and the fate of the native land. The author’s prayers of Wіra Wowk also have a wide palette of artistic means, namely: biblical reminiscentism (introduction to the text of allusions and symbols from the Old and New Testament), synthesis of poetry and prose (to reproduce the dialogue between earthly and heavenly), symbolism and metaphorical, thanks to which in a few words it is possible to express a deep meaning. Especially brightly these funds are reflected in the poetry of Wіra Wowk. These are verbal prayers and prayers without words (colors, sounds of musical instruments), as well as prayer speech and silence prayer, prayer acts and prayer contemplation. In Wіra Wowk’s poetry there is a distinct and unusual image of the Creator God, embodied in the symbolic guises of the Master, the Gardener, the Jeweler, the Astronomer, the Builder, the Film Director, whom no one sees, and the Captain on the river of life. The analysis shows that the genre of prayer is an integral component of the artistic thinking of Wіra Wowk. The literary prayers of the writer are not copies of canonical texts, but are original works.

У статті охрактеризовано ідейно-естетичні та жанрово-стильові особливості авторської молитви Віри Вовк. Встановлено наявність у доробку письменниці великого корпусу текстів молитовного змісту (переважно поезій). Наголошено, що більшість літературних молитов авторки – це оригінальні новотвори, а не інтерпретації канонічних молитовних формул. З’ясовано витоки жанру молитви та проаналізовано специфіку його втілення у прозі, поезії та драматургії Віри Вовк.
АВТОРСЬКА МОЛИТВА У ТВОРЧОСТІ ВІРИ ВОВК
Keywords: Wіra Wowk; author’s prayer; artistic thinking; aphorism; metaphor; image; symbol; Віра Вовк; авторська молитва; художнє мислення; афористичність; метафора; образ; символ